INFLUENCE OF GENE ACTION IN DIALLEL CROSSING ON BOTTLE GOURD [LAGENARIA SICERARIA (MOL.) STANDL] HYBRIDS - ANIL KUMAR; G. C. YADAV; RAM PRASAD; ANAND KUMAR SINGH (The Bioscan, 2014)
In present study, diallel cross analysis was carried out for development of Hybrid in Bottle Gourd (Lagenaria siceraria (Mol.) Standl. The gene effects with respect to its nature and magnitude for yield and yield contributing traits (12 characters) were studied by involving 45 hybrids obtained by crossing 10x10 half diallel pattern. The estimates components of variance and their related statistic for different characters especially fruits per plant (6.45*±0.97) and fruit yield per plant (2.12*±0.43) have been found significant (p<0.05) for dominance components H1 . The values of additive components D were also significant (p<0.05) for most of the characters except for no. of fruits per plant and fruit yield per plant (kg). These results indicate importance of both additive and dominance gene action in expression of these characters. The average degree of dominance (H1/D) 1/2 involved in the action of genes was found as over dominance for all the traits.